Counterinsurgent Warriors - Hurtado Meza, Lourdes Cecilia (2025)
This article examines the early history of the Peruvian rangers, the commandos, at the beginning of the 1960s. I suggest that the foundation of the School of Commandos shaped a new way of being a military man in Peru, which was more aggressive, performative, and with an emphasis on the destruction of the enemy to defend the motherland. Although this new paradigm of being a soldier was spread to the rest of the armed forces in the 1960s and 1970s, its most lethal features were contained because Peru lived in a situation of peace. However, the internal conflict that Peru experienced between 1980 and 2000 facilitated the spread of violent practices associated with the Special Forces. The war originated a phenomenon that I have called the «commandization» of the Peruvian army. During the internal conflict, thousands of drafted men were exposed to the most lethal aspects of a military culture that had been taking shape since the 1960s.